Pengaruh Iklan dan Brand Image MS. Glow terhadap Minat Beli Konsumen: Effect of Advertising and Brand Image MS. Glow Against Consumer Purchase Interest of Advertising and Brand Image MS. Glow Against Consumer Purchase Interest - Kholid Albar; Hanis Noviyanti; Dewi Puspita Sari; Ainiyatuz Zakhiroh (STEI Kanjeng Sepuh Gresik Jawa Timur, 2022)
In the era of globalization, it is very important to continue to look for the right formula in business activities, innovation from each business is often shown as part of business competition. The emergence of business structures and strategies using modern innovative approaches contributes to the creation of models that determine the achievement of competitive advantage and optimal revenue generation, so the company must be able to implement the right strategy in order to attract more visitors. The purpose of this study was to determine the effect of advertising and brand image variables simultaneously or partially on consumer buying interest in MS products. Glow and to find out which mix of Advertising and Brand Image MS. Glow is the most dominant in influencing consumer buying interest. Respondents were 100 people. Data were collected using an instrument in the form of a questionnaire. The data analysis technique used is multiple linear regression analysis. The conclusion of this study is that together the independent variables have a positive and significant effect on consumer buying interest in MS products. glow. On its own, the variables that have a positive effect are advertising and brand image. The dominant variable of the mix on consumer buying interest is advertising.